University Students’ Perspective on English Speaking Challenges: A Descriptive Study - Rahman, Aulliya’; Hamid, Muhammad; Farich Hizbana, Achmad; Halik, Nurdin; Budianto, Lestari (JET ADI BUANA, 2024)
Speaking English can be something very challenging, including for students. This research aims to reveal the challenges experienced by students regarding English speaking activities. This research involved three participants from Abdul Chalim University. This research uses descriptive qualitative research methods and research data is collected through interviews and observation. The results of this research show that there are three main challenges in speaking English for students. The first is Lack of English-Speaking Environment. The second is Uncertainty in Pronunciation and Grammar. The third is Lack of Confidence. This research holds significance in understanding the challenges of English speaking among university students and contributes to the development of more effective educational solutions. However, this research has limitations in the number and variety of research participants. Therefore, it is recommended for future research to conduct similar research by increasing the number and variety of research participants.